Exercise Therapy for People With Sarcopenic Obesity: Myokines and Adipokines as Effective Actors - Alizadeh Pahlavani, Hamed (Frontiers in Endocrinology, 2022)
Sarcopenic obesity is defined as a multifactorial disease in aging with decreased body muscle, decreased muscle strength, decreased independence, increased fat mass, due to decreased physical activity, changes in adipokines and myokines, and decreased satellite cells. People with sarcopenic obesity cause harmful changes in myokines and adipokines. These changes are due to a decrease interleukin-10 (IL-10), interleukin-15 (IL-15), insulin-like growth factor hormone (IGF-1), irisin, leukemia inhibitory factor (LIF), fibroblast growth factor-21 (FGF-21), adiponectin, and apelin. While factors such as myostatin, leptin, interleukin-6 (IL-6), interleukin-8 (IL-8), and resistin increase. The consequences of these changes are an increase in inflammatory factors, increased degradation of muscle proteins, increased fat mass, and decreased muscle tissue, which exacerbates sarcopenia obesity. In contrast, exercise, especially strength training, reverses this process, which includes increasing muscle protein synthesis, increasing myogenesis, increasing mitochondrial biogenesis, increasing brown fat, reducing white fat, reducing inflammatory factors, and reducing muscle atrophy. Since some chronic diseases are not able to do high-intensity strength training, exercises with blood flow restriction (BFR) are newly recommended. Numerous studies have shown that low-intensity BFR training produces the same increase in hypertrophy and muscle strength such as high-intensity strength training. Therefore, it seems that exercise interventions with BFR can be an effective way to prevent the exacerbation of sarcopenia obesity. However, due to limited studies on adipokines and exercises with BFR in people with sarcopenic obesity, more research is needed.